Substance use among Indian Physicians: A narrative review - Yesh Chandra Singh; Roshan Bhad; Arun Kandaswamy (Indian Journal of Psychiatry)
Background: Substance use disorders (SUDs) are a global public health problem with more adverse impacts among the population at risk. Healthcare workers, including physicians, are at increased risk of substance use problems in developing countries, including India, due to prolonged working hours, financial stress due to poor pay during early career, and poor work–life balance. Aim: We conducted a narrative review to assess the rate and pattern of substance use among Indian physicians. Methods and Results: As per limited prevalence studies among Indian physicians since the year 2000, tobacco consumption and alcohol are the most common and have a higher prevalence than the general population. Recent studies also reveal issues with prescription drugs. As physicians entrusted to their patient care, they must follow the code of medical ethics, fulfilling the profession’s duties. This creates complex situations in the management of the problem, medical fitness, and stigma. Conclusion: The present narrative review assesses the prevalence of substance use among physicians in India. Some of the management and ethical issues in this “special population” group are discussed, referring to available literature in other countries, while discussing a way forward for the Indian setting.